Recursos didácticos para el desarrollo de la motricidad fina en niños de primer año de educación básica - Pereira Paredes, Lucitania Jackeline (2018)
In the present learning in students run through manipulation, navigation, communication and discovery; the activities and the use of concrete material in the classroom makes the interaction and the abstraction of contents that help to ensure the fulfilment of the different phases of learning, it is important to plan activities that trigger the teaching making children to reflect through the manipulation of concrete objects. In the first years of life motor skills plays a very important role in children, affecting a valuable contribution in the development of intellectual, affective and social development that will allow you to interact with the environment, as the infant grows has new tasks to learn and physical challenges to overcome in where the family plays a significant role in the stimulation of activities that strengthen the fine motor skills. The implementation of teaching resources has a direct relationship with the pedagogy, whose intention is to awaken in children the imagination, creativity, participation and development of programming with the use of different materials that enable you to deploy the fine motor skills and strengthen their knowledge. In this sense, the teaching in the school processes is fundamental to the development of abilities and skills in the children being important the use of didactic resources to permit the development of fine motor skills that later will allow the learning of reading and writing as an element of formation of knowledge by taking advantage of the dynamism of the parvulitos at this stage. In this sense this research aims to establish teaching resources for the development of fine motor skills in children of first year of basic education from direct observation to enhance the learning process. The approach applied in this research is empirical inductive, because it is important from the observation of the object to investigate. The method was qualitative-quantitative in nature, because it described the research and then quantified by applying a participatory observation guide this facilitated detect the problem in the School of Basic Education "Colonel Félix Vega Dávila," in order to obtain the information on the activities carried out by children in the programming for the development of fine motor skills, as well as an interview teachers in where he was able to identify that some are not trained in due course on teaching resources entertainment to develop fine motor skills of children, applying only the knowledge that gives them the ministry of education, which is limited by its workload. Considering the above prepared a proposal on the innovative plan of activities to develop motor skills and encourage teachers to be trained on the management of these activities and the dynamic and practical utility that have in the development of learning for children in that school and thus strengthen the deficiencies found in this research process, and was able to identify that some playful learning resources such as: peak of bottles with caps, Light Table, porta pompoms of colors and figures of nuts and trees help you to streamline and enhance the knowledge for the acquisition of autonomy in the different daily activities, being essential that these resources are applied throughout the process of Training.